Managing Penicillin Allergy in Primary Care: An Important but Neglected Aspect of Antibiotic Stewardship - Marta Wanat; Sibyl Anthierens; Marta Santillo; Catherine Porter; Joanne Fielding; Mina Davoudianfar; Emily Bongard; Ly-Mee Yu; Christopher Butler; Louise Savic; Sinisa Savic; Johanna Cook; et al. (Medical Sciences Forum, 2023)
An estimated 2.7 million people in the UK are potentially prevented from accessing highly effective and inexpensive penicillins as a result of incorrect penicillin allergy records. Removing incorrect penicillin allergy records may lead to improved patient outcomes and contribute to the tackling of antibiotic resistance. We aim to develop and evaluate whether the ‘Penicillin Allergy Assessment Pathway’ (PAAP) is effective in improving patient outcomes. At the first stage of this work, we have focused on understanding patients’ and primary care clinicians’ views of attending and referring to penicillin allergy testing, and then prescribing and consuming penicillin following a negative test result.